THE ROLE OF TRAINING DEVICES IN TEACHER PROFESSIONAL DEVELOPMENT - Arnosti, Rebeca [UNESP]; de Souza Neto, Samuel [UNESP] (FapUNIFESP (SciELO), 2023)
The aim of this study was to analyze training devices and see what role they play in teachers’ professional development. We carried out a qualitative study with a constructive-collaborative approach through participant observation, focus groups and questionnaires involving 3 schools and 92 subjects. We identified and produced student monitoring devices and socio-professional monitoring devices. It turned out that the devices straddle the fine line between being bureaucratic and/or generating formative meanings. It proved to be important to (re)develop them collecti-vely and have socio-professional support from those coordinating the process. In successful situations, the devices have assisted the school’s organizational development.
EL PAPEL DE LOS DISPOSITIVOS FORMATIVOS EN EL DESARROLLO PROFESIONAL DOCENTE
LE RÔLE DES DISPOSITIFS DE FORMATION DANS LE DÉVELOPPEMENT PROFESSIONNEL DES ENSEIGNANTS
Keywords: IN-SERVICE TEACHER TRAINING; ORGANIZATIONAL DEVELOPMENT; PROFESSIONAL DEVELOPMENT